The immigrant paradox and math self-concept: An SES-of-origin-country hypothesis. (February 2022) - Basarkod, Geetanjali; Marsh, Herbert W.; Parker, Philip D.; Dicke, Theresa; Guo, Jiesi
Abstract: The immigrant paradox is the phenomenon where recent immigrants have better outcomes than individuals from native-born families. Although limited past research has shown the paradox to exist for math self-concept, neither its exact nature nor a theoretical explanation for its existence have been reported. Using Australian cohort data from the Programme for International Student Assessment (PISA) 2003 ( N = 12, 551) and 2012 ( N = 14, 481), we first establish that immigrant students have higher math self-concepts than native students, controlling for gender and absolute parental socioeconomic status (SES), and show that it is similar to—albeit weaker than—the expectation-achievement gap. We then provide an SES-of-origin-country hypothesis as a contextual explanation for this effect; we show that the immigrant paradox for both math self-concept and educational expectations substantially reduces when accounting for parents' SES relative to their country-of-origin. Our findings suggest that the paradox for math self-concept and educational expectations may partly result from immigrant parents' socioeconomic advantage in their home countries. Highlights: We test the immigrant paradox for math self-concept in two Australian PISA cohorts. Immigrants had higher math self-concepts than native students, controlling for parental SES. This paradox was similar to, but smaller than, the expectation-achievement gap. The SES of parents' origin country helped explain both the paradox and the gap. This country-of-origin contextual effect was robust to sensitivity analyses.